HUBUNGAN RESISTENSI ASPIRIN DAN HIPERTENSI PADA PASIEN STROKE ISKEMIK BERULANG - , Feolistin Mience Pobas ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Aspirin is an antiplatelet agent that is widely used in patients with ischemic stroke. However, approximately 15 - 25% of patients are resistant to aspirin. Hypertension is thought to be the cause of aspirin resistance because hypertension can lead to increase blood viscosity and platelet aggregation by reducing the antiplatelet effectiveness of aspirin. Besides hypertension, antihypertensive drugs such as ACEI and ARB can also cause aspirin resistance by increased platelet aggregation. Objective: Study the relationship between hypertension and antihypertensive drug use on the aspirin resistance in recurrent ischemic stroke patients. Methods: This study is a descriptive study with a nested case-control study design. This study compared the resistance aspirin in recurrent ischemic stroke patients with non aspirin resistance in recurrent ischemic stroke patients based on the results of the VerifyNow on aspirin reaction unit value (ARU). Patients with ARU value â¥ 550 are grouped into subject groups (aspirin resistance) and into patients with ARU value < 550 are grouped into control group (non resistance aspirin). Searching medical records and registers stroke to known patients characteristics. The results will be analyzed using bivariate and multivariate analyzes. Results: A total 86 recurrent ischemic stroke patients were identified by VerifyNow test. The result 78 patients were inclusion. From 78 patients, 16 (20.5%) patients had aspirin resistance. Bivariate analysis result showed hypertension and antihypertensive drug use has no relationship on the incidence of aspirin resistance. Although ACEI had no effect on the incidence of aspirin resistance (p = 0.050